Innovations, reinvented politics and representative democracy - Alexandre, Agnès; Goujon, Alexandra; Gourgues, Guillaume (Democratization studies, 2020)
"This volume focuses on the issue of change in democratic politics in terms of experimental or actual innovations introduced either within political parties or outside the party system, involving citizen participation and mobilization. Including a wide and diverse range of alternatives in the organization of groups, campaigning, conducting initiatives and enhancing practices, they not only question the relevance of traditional institutions in representing citizens' values and interests, but also share a common goal which is precisely - and perhaps paradoxically - to reshape and invigorate representative democracy. This book is of key interest to scholars and students of party politics, elections/electoral studies, social movement and democratic innovations and more broadly to comparative politics, political theory and political sociology"